Audit of Endotracheal Tube Suction in a Pediatric Intensive Care Unit. (February 2017) - Davies, Kylie; Bulsara, Max K.; Ramelet, Anne-Sylvie; Monterosso, Leanne
We report outcomes of a clinical audit examining criteria used in clinical practice to rationalize endotracheal tube (ETT) suction, and the extent these matched criteria in the Endotracheal Suction Assessment Tool(ESAT)©. A retrospective audit of patient notes ( N = 292) and analyses of criteria documented by pediatric intensive care nurses to rationalize ETT suction were undertaken. The median number of documented respiratory and ventilation status criteria per ETT suction event that matched the ESAT© criteria was 2 [Interquartile Range (IQR) 1-6]. All criteria listed within the ESAT© were documented within the reviewed notes. A direct link was established between criteria used for current clinical practice of ETT suction and the ESAT©. The ESAT©, therefore, reflects documented clinical decision making and could be used as both a clinical and educational guide for inexperienced pediatric critical care nurses. Modification to the ESAT© requires "preparation for extubation" to be added.